Historic landmarks in the development of Agricultural Land Market in Poland after the year 1989 - Majewski, Edward (Applied Studies in Agribusiness and Commerce, 2008)
For a number of decades in the second half of the XXth century, agricultural land has been divided in Poland between three sectors: family, state owned and cooperative farms, with a dominating share of private, individual farmers in land use. As a result, ownership structure of agricultural land in Poland is quite unique among the former socialist Central and East European countries. Until the year1989, when the transformation to a market economy was initiated, the land market in Poland was almost non-existent. The State Land Fund(SLF), an institution created in 1944 was fordecades a substitute to land market. Originally, the Fund was responsible for the implementation of the land reform. After nationalization or confiscation of real estates, state farms have been established on a larger part of agricultural land under Fund’s management. Therest has been divided between formerfarm workers and small farmers owing less than 5 hectares of land.